Proteomic Analysis of Paracoccidioides brasiliensis During Infection of Alveolar Macrophages Primed or Not by Interferon-Gamma - Chaves, Edilânia Gomes Araújo; Parente-Rocha, Juliana Alves; Baeza, Lilian Cristiane; Araújo, Danielle Silva; Borges, Clayton Luiz; Oliveira, Milton Adriano Pelli de; Soares, Célia Maria de Almeida (Frontiers in Microbiology, 2019)
Although members of the Paracoccidioides complex are not obligate intracellular pathogens, they present the ability to survive and multiply inside epithelial cells and phagocytes of mammals, which may favor the spread of the fungus in host tissues. Macrophages resident in the lung are the first line of defense against paracoccidioidomycosis (PCM), presenting mechanisms to control the pathogen dissemination through the granuloma formation or eliminating the fungus through phagocytosis. Phagocytosis triggers an oxidative burst, in which there is an increase in the production of toxic elements, derived from oxygen and nitrogen. The interior of the phagolysosome is a harsh environment to the internalized pathogens, since in addition to the oxygen and nitrogen reactive species, microorganisms face nutrient shortages and proteases activity. Through the NanoUPLC-MSE technology, we analyzed the proteomic response of Paracoccidioides brasiliensis during the infection of alveolar macrophages primed or not by interferon gamma (IFN-γ). At 6 hs post-infection, only (IFN-γ)-primed macrophages were able to kill the fungus. We observed the regulation of amino acids degradation, tricarboxylic acid cycle, respiratory chain, ATP synthesis, glyoxylate cycle, as well as an increase in the expression of defense proteins related to oxidative stress, heat shock, and virulence factors under both conditions analyzed. However, some pathways described as essential for the survival of pathogens inside macrophages were observed only or with higher intensity in yeast cells recovered from non-primed macrophages, as phosphate pentoses pathway, methylcitrate cycle, synthesis of cell wall components, and mitochondrial activity. The data indicate that the intracellular environment of non-primed macrophages could be more permissive to the survival and multiplication of P. brasiliensis. The identification of key molecules for the establishment of infection can help the understanding of the nature of the parasite–host relationship and pathogenesis of PCM.